Foliar Application of Melatonin Improves Photosynthesis and Secondary Metabolism in Chenopodium quinoa Willd. Seedlings Under High-Temperature Stress - Meiqing Li; Jinyang Li; Deke Xing; Yanyou Wu (Agronomy, 2025)
The suitable growth environment for quinoa is high-altitude areas. In recent years, quinoa is also gradually cultivated in other regions with high-temperature exposure. High-temperature stress poses a potential constraint on quinoa quality and yield by impacting pigments, photosynthesis, and metabolites. This study aimed to investigate the effect of exogenous melatonin (MT) in alleviating heat stress on quinoa in controllable conditions. Day/night temperatures were maintained at 35/25 °C in a climate chamber, and foliar spraying was performed using melatonin (MT) concentrations of 0, 50, 100, and 200 μmol L−1. Day/night temperatures were maintained at 25/15 °C in another climate chamber as a comparative trial. Our results demonstrated that high temperature decreased the levels of photosynthetic pigments and the values of photosynthetic rate (Pn), stomatal conductance (gs), and transpiration rate (Tr). Additionally, it also influenced the accumulation of polyphenols and altered polyphenol oxidase (PPO) activity in the red quinoa (RQ) cultivar. Obvious reductions in gas exchange parameters and metabolites including flavonoid, anthocyanin, and PPO were observed both in the BQ cultivar and the WQ cultivar. However, the application of 100 μmol L−1 MT significantly increased the levels of photosynthetic pigments, the values of Pn, gs, and Tr, and the PPO activity, as well as the contents of flavonoid and anthocyanin in the RQ cultivar. The application of 50 μmol L−1 MT only led to an increase in the concentrations of Chl a, Chl (a + b), and flavonoids, as well as PPO activity, whereas 100 μmol L−1 MT significantly enhanced the values of Pn, gs, and Tr and the PPO activity. Additionally, 200 μmol L−1 MT contributed to the synthesis of anthocyanins and polyphenols, and enhanced PPO activity in the BQ cultivar. The application of 50 μmol L−1 MT limited the increase in the contents of total polyphenols, flavonoids, and anthocyanin, we all as PPO activity, in the WQ cultivar. The findings demonstrated that photosynthesis and metabolite synthesis in quinoa under high temperatures depends on an interactive response between cultivar and melatonin levels. The application of 100 μmol L−1 MT was found to be optimal for alleviating the adverse effects of high temperature on photosynthesis and metabolites in the RQ cultivar during actual production.